2010
DOI: 10.1111/j.1465-7295.2010.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Trade Costs in Deviations From the Law‐of‐one‐price: Estimates Based on the Direction of Trade

Abstract: The full impact of trade costs in segmenting product markets cannot be captured by considering aggregate prices or in the absence of information on the direction of trade. We address this problem by utilizing product‐specific prices, cross‐sectional productivity indices, and bilateral trade flows, allowing us to identify the probable source of any one product. We show that trade costs in the form of transportation and distribution costs are important in determining international price differences and segmentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The data on prices of goods, needed for the estimation of sectoral θ's, come from Eurostat surveys of retail prices in the capital cities of EU countries for the year 1990. The data set has been compiled by Crucini, Telmer, and Zachariadis (2005) and used by Giri (2012), Inanc and Zachariadis (2012), and Yorukoglu (2000). 11 We use price data for 12 countries included in the surveys -Austria, Belgium, Denmark, France, Germany, Greece, Ireland, Italy, Netherlands, Portugal, Spain and United Kingdom.…”
Section: Data For Estimating Sectoral Trade Elasticities Trade Costsmentioning
confidence: 99%
“…The data on prices of goods, needed for the estimation of sectoral θ's, come from Eurostat surveys of retail prices in the capital cities of EU countries for the year 1990. The data set has been compiled by Crucini, Telmer, and Zachariadis (2005) and used by Giri (2012), Inanc and Zachariadis (2012), and Yorukoglu (2000). 11 We use price data for 12 countries included in the surveys -Austria, Belgium, Denmark, France, Germany, Greece, Ireland, Italy, Netherlands, Portugal, Spain and United Kingdom.…”
Section: Data For Estimating Sectoral Trade Elasticities Trade Costsmentioning
confidence: 99%
“…Table reports detailed information about data availability for the different cross‐sections and for the panel we put together. Both CTZ and Inanc and Zachariadis () utilize the first four cross‐sections of the Eurostat price data for 1975, 1980, 1985, and 1990. The Eurostat survey covers nine countries for 658 goods in 1975, 12 countries for 1,090 goods in 1980, 13 countries for 1,805 goods in 1985, 13 countries for 1,896 goods in 1990, 31 countries for 2,505 goods in 2005, and 37 countries for 2,414 goods in 2010.…”
Section: Data and Preliminary Analysismentioning
confidence: 99%
“…We have shown that the process of European integration as captured by the proximity of prices 10 We thank an anonymous referee of this journal for pointing this out. Results from this exercise are available upon request.…”
Section: Resultsmentioning
confidence: 85%
“…This is useful as if persistence values turn out to be higher for non-tradeables it would provide justification for the use of percentages as a proxy for persistence. 10 Indeed, price advantage appears overall to be more persistent for non-tradeables than for tradeables in relatively poorer countries, and price disadvantage more persistent for non-tradeables than for tradeables in relatively rich countries. 11…”
Section: Resultsmentioning
confidence: 99%